Perbandingan Pemilu 1955 dengan Pemilu 1999: Realitas Partai Politik dan Kualitas Pemilu - Komalasari, Kokom (Jurnal Civicus, 2003)
Perbandingan Pemilu 1955 dengan Pemilu 1999: Realitas Partai Politik dan Kualitas Pemilu